PELAKSANAAN PROYEK REHABILITASI JARINGAN IRIGASI ( DAK ) DAERAH IRIGASI CIBUTUL - Hidayat, Lutfi; Laila Nurjamilah, Lia (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2021)
Rehabilitation of Cibutul Irrigation Area, located in Sukahaji Village, Sukahaji District, Majalengka Regency is a package of work for the Rehabilitation of Irrigation Networks / DAK. It is one of the efforts to restore the function of the irrigation because the malfunction or damage of one of the irrigation structures will affect the performance of the existing irrigation system, resulting in decreased irrigation efficiency and effectiveness. Implementation of rehabilitation work for Cibutul Irrigation Area with scattered work points. The work carried out included making gabions, repairing sabodam wings and repairing linging pairs in the main and secondary channels.